"Pragmatic yet principled" : an assessment of Botswana's foreign policy record as a small state - Mahupela, Kabelo Moganegi (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
International Relations (IR) theory has traditionally downplayed the capabilities of small states, focusing rather on how the behaviour of large powers dictates interactions of actors within an anarchic arena. This has been very much the case for the realist/neorealist and to a very large extent neoliberal canons of IR, which privilege the structure of the international environment ahead of the agency of actors. As such, the foreign policy analysis of smaller powers in IR "“ and especially that of African countries "“ has been marginalised to the periphery. In response to these oversights, constructivism has posited a set of theories in which state identities and interests are determined by an inter-subjective interactive process that gives meaning to the material world. These set of theories also point out that norms can constrain and indeed energise state behaviour in a socially constructed world. This has thus opened up a space within which small state foreign policy behaviour can be analysed "“ whether it is through conference diplomacy, negotiation skills or idiosyncratic behaviour predicated upon elite ideas and identities. This thesis draws upon the above framework to assess a number of foreign policy choices embarked upon by Botswana in which she has leveraged herself vis-Ã -vis more powerful actors. The study looks at how Botswana managed to break out of its hostage station within Southern Africa during apartheid, at a time when Gaborone was surrounded by unfavourable white minority rule (in South Africa, Rhodesia, Angola and Mozambique). The study also evaluates Botswana"Ÿs leveraging of her favourable image perception amongst powerful actors, as well as her negotiation proficiency in managing to punch above her weight and obtain favourable outcomes "“ thereby mitigating the desperate economic conditions she had inherited from colonialism. In a time where much of Southern Africa (and indeed the continent as a whole) disregard and actively disrupt normative imperatives related to democracy, human rights and the rule of law, the thesis also assesses Botswana"Ÿs principled foreign policy posture. Through these chapters, it will be demonstrated that Botswana is an example of a state that has managed to use a careful combination of pragmatism and principle to show that African small states can indeed exercise agency.
Keywords: Constructivism (Philosophy); Botswana -- Foreign relations; States, Small -- Economic conditions; States, Small -- Politics and government; Africa -- Politics and government; Africa -- Foreign relations